Technology-Based Change Management: The Potential of Social Media in Public Sector Transformation - Manuain, Alfandy Florian; Fanggidae, Ivan Gideon; Pandie, Ardy Yosafat (Journal of Governance and Administrative Reform, 2025)
Abstract This research examines the utilization of social media by Regional Government Organizations (Organisasi Perangkat Daerah, OPD) in the City of Kupang, focusing on its potential to enhance transparency, accountability, and public participation in governance processes. Adopting a qualitative approach through an embedded single-case study design, the study aims to provide a comprehensive understanding of the challenges and opportunities associated with the integration of social media in public administration. Data were gathered through interviews, document analysis, and direct observation, with the analysis involving categorization, interpretation, and inductive reasoning. The findings suggest that although social media offers significant opportunities for improving public engagement and facilitating real-time communication, its implementation faces considerable obstacles. These challenges include organizational resistance, inadequate digital competencies among staff, and the absence of a well-defined strategy. The study underscores the critical role of strategic change management, emphasizing continuous capacity building, transformational leadership, and a robust communication framework to effectively address these challenges. This research contributes to the growing body of knowledge on the role of social media in modernizing local governance and highlights the importance of aligning organizational culture to foster technological innovation. By addressing the knowledge gap regarding digital transformation in regional bureaucracies, the findings offer practical insights for policymakers and provide a foundation for future comparative studies across different regions. Keywords: change management; public governance; social media.     Abstrak  Penelitian ini mengkaji pemanfaatan media sosial oleh Organisasi Perangkat Daerah (OPD) di Kota Kupang, dengan fokus pada potensinya untuk meningkatkan transparansi, akuntabilitas, dan partisipasi publik dalam tata kelola pemerintahan. Penelitian ini menggunakan pendekatan kualitatif dengan desain studi kasus tunggal embedded untuk memperoleh pemahaman yang komprehensif mengenai tantangan dan peluang adopsi media sosial dalam administrasi publik. Pengumpulan data dilakukan melalui wawancara, analisis dokumen, dan observasi, dengan analisis data melibatkan kategorisasi, interpretasi, dan penalaran induktif. Temuan menunjukkan bahwa meskipun media sosial menawarkan peluang besar untuk meningkatkan keterlibatan publik dan komunikasi secara real-time, implementasinya menghadapi tantangan signifikan, termasuk resistensi organisasi, keterbatasan keterampilan digital pegawai, dan ketiadaan strategi yang terstruktur. Penelitian ini menyoroti pentingnya manajemen perubahan strategis yang mencakup pengembangan kapasitas berkelanjutan, kepemimpinan transformasional, dan kerangka komunikasi yang lebih baik untuk mengatasi hambatan tersebut. Studi ini memberikan kontribusi pada pemahaman peran media sosial dalam memodernisasi tata kelola lokal dan menekankan pentingnya adaptasi budaya organisasi untuk mendukung inovasi teknologi. Dengan menjembatani kesenjangan pengetahuan terkait transformasi digital dalam birokrasi daerah, temuan ini memberikan implikasi praktis bagi pembuat kebijakan dan menjadi referensi bagi studi komparatif lebih lanjut di wilayah lain. Kata kunci: manajemen perubahan; tata kelola publik; media sosial.